Integration of Banks and Financial Institutions in Disaster Risk Financing: A Pathway to Strengthen Nepal’s Resilience - Adhikari, Sony; Rajkarnikar, Rashmee Shilpakar (Economic Journal of Nepal, 2024)
This paper reviews the theoretical basis of key Disaster Risk Financing approaches and evaluates their use in Nepal, drawing on existing literature, national policies, practices, and secondary data. Findings show that Nepal has incorporated some Disaster Risk Financing components into its policy framework, but implementation remains limited. Institutional fragmentation, capacity gaps, and low stakeholders’ awareness make these tools less effective. Banking and Financial Institutions contribute only marginally, with Disaster Risk Financing showing feeble performance on risk pooling, risk transfer, liquidity management, and timely fund disbursement. Regulatory bodies such as Nepal Rastra Bank and the Ministry of Finance have yet to introduce binding policies, guidelines, or incentives to integrate Banking and Financial Institutions in the national Disaster Risk Financing framework. The absence of innovative financial tools and institutional direction has created persistent gaps. The paper points out the necessity of a more integrated Disaster Risk Financing framework and stronger involvement of the banking and financial system through coordinated regulatory action, policy alignment, and capacity strengthening to increase fiscal resilience.